Modos de ler do professor em contexto de uma prática de leitura de formação continuada: uma análise enunciativa - Horikawa, Alice Yoko (2006)
This investigation, grounded on the presuppositions of the collaborative research, as discussed by Magalhães (2004; 2002; 1999; 1996), was held in spaces of continuous formation of a public school of the municipal district of São Paulo, aiming to promote the reading of primary scientific and of scientific popularization texts. The analysis work is guided by the objective of investigating the manners of reading proceeded by six educators and the relationship between those manners and the critical-reflexive teacher's formation. It is, also, our interest to analyze the process of construction of senses, being considered the social voices put into action by the participants in the dynamics of appropriation of the author's of the read text saying. The theoretical framework concerns to the themes of the teachers' formation and of reading and language. As for the first, we presented, based on authors as Marcílio (2005), Borges (2005), Nosella (2005), and Ribeiro (2003), the history of the teachers' formation in Brazil and the formation conceptions that are in opposition to the technicist tendency that marked this history in order to stress here the value of the critical-reflexive formation, according to approach defended by authors as Libâneo (2002), Pepper (2002), Giroux (1998), and Contreras (1999). In relation to the theme of reading and language, we appealed, initially, to the field of the History of the Reading, represented mainly by Chartier (1985; 1997), Hébrard (1985), Manguel (1996), Anne-Marie Chartier, and Hébrard (1995), to build the understanding that the reading is related to a singular work of signification of the utterance of the other, conformed to the context in what the activity takes place and to the reading practices built along man's history in his relationship with the written text. In order to demonstrate the breadth of these studies in the discussion concerning teacher´s reading, we based by authors as Kleiman (2001), Batista (1999), and Britto (1998). Grounded on Vygotsky (1925; w/d; 1934), Volochinov/Bakhtin (1926), Bakhtin/Volochinov (1929), and Bakhtin (1934-35; 1952-53) our study searches to situate the conception of reading defended by reading historians in its enunciative dimension. The discussion of the data points out for the importance of analyzing the teacher's reading in the relationship with the context in which this develops in order to consider the specific demands of the educational work and the valorative appreciation that the professionals, as subjects historically and culturally situated, elaborate in regarding to the saying of others. From this perspective, the participants of this research show themselves as competent readers as far as they transform the text in resource to understand their practice, to question proposals, and to look for their adjustment to the private situation in which they are inserted